Pengaruh Ukuran Pemerintah Daerah, Kekayaan Pemerintah Daerah, Dan Jumlah Penduduk Terhadap Pengungkapan Internet Budgeting Reporting - Deka Anugrah Hadi; Mia Angelina Setiawan (Jurnal Eksplorasi Akuntansi, 2020)
Internet budgeting report is considered still have shortcomings because it is not in accordance with the Instruction of the Minister of Domestic. Even though this information is the responsibility of regional governments for transparency in regional management and avoiding budget leakage. This study aims to determine the effect of local government size, local government wealth, and population on internet budgeting reporting, There is difference in this study which are sample taken from district / city governments on the island of Sumatra. The district / city governments should has an official website for public access. The sampling technique was purposive sampling. A total of 154 districts / cities were used as sampled in this study and processed by using multiple linear regression techniques. The study results indicate that the local government size has a positive and significant effect on internet budgeting reporting. While local government wealth and population does not have a significant effect on internet budgeting reporting. Future studies are suggested to examine other variables that can affect internet budgeting reporting so that they can predict more accurately and expand the research sample